Meningkatkan Minat Belajar Matematika Dengan Metode Belajar Sambil Bermain - Novita Andriani Panjaitan; Agus Suriadi (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
Positive learning experiences stem from active engagement with lessons and greater interaction in learning activities. Play is also important for development because it contributes to the cognitive, physical, social and emotional well-being of children. Therefore the method of learning while playing is a good learning method and can be applied to learning mathematics. The purpose of this Field Work Practice is to motivate children in learning, especially in mathematics. The use of learning while playing methods like this can increase children's interest in learning so they don't feel bored and have more fun when learning math. The intervention used in this practicum activity is a mezzo intervention using the group work method through general or general stages which consist of; Engagement Intake Contract, Assessment, Planning, Intervention, Evaluation, and ending with Termination.